Compact planar folded dipole for wireless application - Mohamed Ariff Hafizal Mat Nasir (Universiti Malaysia Perlis, 2008)
Antenna miniaturization for mobile wireless applications has recently drawn a lot of attention. since the technology in communication increased and the size of the devices has been reduced to be smaller than it normal size. In order fulfill the requirement to be graduated in degree of engineering for the final year the compact planar folded dipole antenna is designed and tested. For design purpose MicroWave is used for designing the layout of antenna and simulation to evaluate it performance before the antenna is fabricate. Fabrication of antenna is done using wet-etching method, on FR-4 dielectric. After fabrication process is complete the antenna is being tested to observe it perfomance.The designed antenna which it frequency resonant is 1.78Ghz is capable to operate in DCS 1800. The testing for the design antenna is done at UniMAP laboratory, the equipment used for testing is such as network analyzer,spectrum analyzer, signal genarator and LPA(log periodic antenna). Antenna testing is important for evaluation of the antenna performance and for comparison to the simulation design.